Memperkuat Kelembagaan Kerjasama Antar Daerah Melalui Perspektif Trust Dan Modal Sosial - Agustinus Bima Nugraha (Program Studi Pembangunan Masyarakat Desa (D3), 2022)
The limitations of local governments in fulfilling public or economic services, etc., have an impact on the inequality of distribution of development results and public services. Therefore, it is important to have Inter-Regional Cooperation to cover the limitations of inequality in economic development, environmental problems and limited regional potential. From some methodological used by previous researchers, they are founded the problems of cooperation, but neglected to see what factors influenced the failure of cooperation. From these problems, the author relates the perspectives of trust and social capital as resources that can be used by actors to help them achieve their goals. The method used by the author is descriptive with a library research approach. In this study, the author uses the literature research method to identify the perspective of trust and social capital in strengthening the inter-regional cooperation institutions in Indonesia. The results of the studies are: First, in the establishment of Inter-Regional Cooperation it is necessary to involve social organizations following Putnam's argument as a support for the established cooperation institutions. Second, the obstacles faced by cooperative institutions in order to realize their goals are due to the weakness of social capital and trust as the basis for building networks between social organizations. Third, trust and social capital are very important values ​​to improve the performance of Inter-Regional Cooperation, especially with regard to costs